The development of Maisha, a video-assisted counseling intervention to address HIV stigma at entry into antenatal care in Tanzania. (December 2020) - Watt, Melissa H.; Knettel, Brandon A.; Knippler, Elizabeth T.; Kisigo, Godfrey; Ngocho, James S.; Renju, Jenny; Rogathi, Jane; Sao, Saumya S.; Minja, Linda; Osaki, Haika; Mwamba, Rimel N.; Mmbaga, Blandina T.
Highlights: Antenatal care is an innovative setting to address community-level HIV stigma. Men can be reached for HIV stigma reduction in the antenatal care setting. Acknowledging stigma prior to HIV testing can help mitigate internalized and anticipated stigma. Abstract: HIV stigma has a profound impact on clinical outcomes and undermines the quality of life of people living with HIV (PLWH). Among HIV-negative individuals, misinformation and prejudicial attitudes about HIV can fuel stigma and contribute to discrimination against PLWH. Antenatal care (ANC), with its focus on universal HIV testing, provides a unique entry point to address HIV stigma. This study describes the development of a counseling intervention to address HIV stigma among women and their partners attending a first ANC appointment in Tanzania. Formative work to inform the intervention consisted of qualitative interviews with 32 pregnant and postpartum women (both women living with HIV and HIV-negative women) and 20 healthcare workers. Data were analyzed iteratively, using a thematic analysis approach, to identify intervention targets. The resulting intervention, Maisha (Swahili for " Life "), includes three sessions informed by the HIV Stigma Framework and Cognitive-Behavioral Therapy: a video and brief counseling session prior to HIV testing and, for those who test seropositive for HIV, two additional sessions building on the video content. A pilot test of the intervention is in process. Addressing HIV stigma at the first ANC visit can help individuals living with HIV to overcome stigma-related barriers to the initiation and maintenance of HIV care, and can reduce stigmatizing attitudes among those who test negative for HIV.